Multicenter study of radiosynoviorthesis - Rau, H.; Lohmann, K.; Franke, C.; Goretzki, G.; Lemb, M. A.; Müller, J.; Panholzer, P. J.; Stelling, E.; Spitz, J. (Nuklearmedizin - NuclearMedicine, 2004)
Aim: Evaluation of the effectiveness of radiosynoviorthesis (RSO) in osteoarthritis and other disorders with concomitant synovitis versus rheumatoid arthritis by means of a standardized questionnaire. Patients, methods: 803 RSO treatments were monitored in 691 patients by standardized questionnaires of 7 centers in 3 countries. Patients were assigned to 3 groups according to their age (20-40, 41-60, 61-80 years). Additionally, the data were analyzed separately for patients with rheumatoid arthritis (group A) and those with osteoarthritis, psoriasis arthritis, pigmental villonodular synovitis or persistent effusions after joint replacement (group B). Results: Ameliorations of joint pain, swelling/effusion or flexibility were found in 80% of group A and 56% of group B (p <0.01). Quality of life improved in 78% of group A and 59% of group B (p <0.01). The response rate was similar for small- and large-sized joints in group A, but significantly higher for large-sized joints in group B (p <0.01). The positive effects on joint pain, swell-ing/effusion or flexibility lasted longer in group A (p <0.01). Repeated RSOs were as effective as initial ones. The clinical outcome was neither influenced by age, nor gender, nor transient immobilisation for 48 hours after RSO. Conclusion: Although slightly more efficient in rheumatoid arthritis, RSO represents an effective treatment option also in osteoarthritis and other disorders with concomitant synovitis.
Keywords: Radiosynoviorthesis; osteoarthritis; arthrosis; synovialitis; arthritis; rheumatoid arthritis